Bioenergetic consequences of FoF1-ATP synthase/ATPase deficiency in two life cycle stages of Trypanosoma brucei - Hierro-Yap, Carolina; Šubrtová, Karolína; Gahura, Ondřej; Panicucci, Brian; Dewar, Caroline; Chinopoulos, Christos; Schnaufer, Achim; Zíková, Alena (The Journal of biological chemistry, 2021)
Mitochondrial ATP synthase is a reversible nanomotor synthesizing or hydrolyzing ATP depending on the potential across the membrane in which it is embedded. In the unicellular parasite Trypanosoma brucei, the direction of the complex depends on the life cycle stage of this digenetic parasite: in the midgut of the tsetse fly vector (procyclic form), the FoF1-ATP synthase generates ATP by oxidative phosphorylation, whereas in the mammalian bloodstream form, this complex hydrolyzes ATP and maintains mitochondrial membrane potential (ΔΨm). The trypanosome FoF1-ATP synthase contains numerous lineage-specific subunits whose roles remain unknown. Here, we seek to elucidate the function of the lineage-specific protein Tb1, the largest membrane-bound subunit. In procyclic form cells, Tb1 silencing resulted in a decrease of FoF1-ATP synthase monomers and dimers, rerouting of mitochondrial electron transfer to the alternative oxidase, reduced growth rate and cellular ATP levels, and elevated ΔΨm and total cellular reactive oxygen species levels. In bloodstream form parasites, RNAi silencing of Tb1 by ∼90% resulted in decreased FoF1-ATPase monomers and dimers, but it had no apparent effect on growth. The same findings were obtained by silencing of the oligomycin sensitivity-conferring protein, a conserved subunit in T. brucei FoF1-ATP synthase. However, as expected, nearly complete Tb1 or oligomycin sensitivity-conferring protein suppression was lethal because of the inability to sustain ΔΨm. The diminishment of FoF1-ATPase complexes was further accompanied by a decreased ADP/ATP ratio and reduced oxygen consumption via the alternative oxidase. Our data illuminate the often diametrically opposed bioenergetic consequences of FoF1-ATP synthase loss in insect versus mammalian forms of the parasite.
Keywords: energetický metabolismus; ATP synthase; bioenergetics; alternative oxidase; Mitochondria; adenosintrifosfát; mitochondria; Proton-Translocating ATPases; protozoální proteiny; Trypanosoma brucei; Trypanosoma brucei brucei; Energy Metabolism; Cell Cycle; respiration; Adenosine Triphosphate; membránový potenciál mitochondrií; buněčný cyklus; Protozoan Proteins; electron transport; ATPase; mitochondrial membrane potential; protonové ATPasy; Membrane Potential, Mitochondrial; mitochondrie; oxidative phosphorylation